Observation of topological transport quantization by dissipation in fast Thouless pumps - Zlata Fedorova (Nature Portfolio, 2020)
Topological quantized transport has been limited to slow varying potentials. Here, the authors report that a topological band structure and associated quantized transport can be restored by non-Hermitian Floquet engineering at a driving frequency as large as the system’s band gap.